A New One-selector One-resistor Verilog-A model for Circuit Simulsation. Issue 1 (March 2020) - Dai, Yuehua; Qi, Min; Tao, Fei; Lu, Wenjun; Yang, Fei
Abstract: In this paper, a compact model of one-threshold switching selector (1S) one-bipolar resistive random-access memory (1R) is developed for 3D memory circuit simulation. Firstly, the mathematical formulas are presented to describe the two different states before and after the threshold switching for S. The formulas are expressed in Verilog-A to develop a S compact model. Secondly, the parameters (Vth1, Vth2, Vop, α, β, Rs ) in the S model are adjusted to match with R. Especially, Vth1 and Vth2 can be adjusted according to the set and the reset voltages of R. Lastly, simulations are conducted in 7T1R circuit and cross-point array performance of the new 1S1R Verilog-A model is analyzed to validate the model performance.